Strategi Manajemen Pemasaran Dalam Meningkatkan Kuantitas Peserta Didik Baru - Himmah, Jaliyatul (Journal of Education Management Research, 2023)
The purpose of this study was to describe the school's marketing strategy in attracting new students at UPT One Roof Public Middle School. This type of research is descriptive qualitative research. The results of the research and discussion of the school's marketing strategy in attracting new students at UPT One Roof Public Middle School can be concluded that the school always tries to carry out school marketing with the following steps: 1) external marketing, carried out by introducing the school to the community, the school always involving all elements or elements, building good communication with all components of education stakeholders in the community regarding the acceptance of new students at school, 2) internal marketing, carried out by always motivating all teachers, administrative staff and students to always do work with full discipline, professionalism, responsibility, love for the work being done, providing effective and efficient service, friendly with a full sense of kinship towards all prospective new students, students' parents and the community. as for the inhibiting factors in the marketing of Education at UPT One Roof Public Middle Schools are 1). Number of New Institutions Around UPT Institutions of One-Stop Public Middle School 2). Tight competition for facilities, 3). Infrastructure facilities are inadequate 4). The interest of new students while the solutions in empowering existing obstacles are 1). Best service 2). Interesting marketing strategy